Możliwości wykorzystania sieci neuronowych w ocenie scoringowej kredytobiorcy - Chluski, Andrzej (The Possibilities of Neural Networks Usage in the Scoring Assessment of Credit Beneficiary, 2007)
The purpose of the paper is to explore in several chosen cases the ability of neural networks in building credit scoring models. The article highlights the neural networks models studies in Polish and foreign banks. As the strength of the studies there can be claimed that it is possible to use neural networks methods for bank's clients classification. The effectiveness of these methods is comparable with classic discrimination methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 217-225